Description of larva and puparium of Oplodontha rubrithorax (Diptera: Stratiomyidae) from the Oriental Region - Nerudová, Jana; Kovac, Damir; Tóthová, Andrea (Zootaxa, 2015)
This is the first description of larva and puparium of Oplodontha rubrithorax (Macquart, 1838) from the Oriental Region. Larvae were found at a hot spring in North Thailand. The morphological features and cuticular structures of the larva are documented by drawings and SEM micrographs and the main characters are compared with the European O. viridula (Fabricius, 1775), the only described larva of this genus. Differences between larvae of both species were only found in pubescence. The characteristic, somewhat dilated and slightly clavate hairs on the dorsal surface of the body segments of O. viridula larva are apparently lacking in the larva of O. rubrithorax.
Keywords: Larva; velikost těla; Diptera; Male; Organ Size; kukla; larva; Animal Structures; Ecosystem; Animals; ekosystém; Animal Distribution; Pupa; zvířata; rozšíření zvířat; mužské pohlaví; Body Size; ženské pohlaví; Female; anatomické struktury zvířat; velikost orgánu